2016
DOI: 10.1007/s00268-016-3633-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Moderate Versus Deep Neuromuscular Block for Low‐Pressure Pneumoperitoneum During Laparoscopic Cholecystectomy

Abstract: The maintenance of intraoperative deep neuromuscular blockade was associated with a lower rate of conversion to standard pressure and higher surgeon satisfaction with the surgical conditions than was moderate blockade in patients undergoing low-pressure pneumoperitoneum laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 29 publications
2
43
3
5
Order By: Relevance
“…We were unable to demonstrate a reduction in the duration of surgery. This is in contrast to our previous study, which showed a significant decrease in the duration of operations with deep compared with moderate neuromuscular block during laparoscopic cholecystectomy .…”
Section: Discussioncontrasting
confidence: 99%
“…We were unable to demonstrate a reduction in the duration of surgery. This is in contrast to our previous study, which showed a significant decrease in the duration of operations with deep compared with moderate neuromuscular block during laparoscopic cholecystectomy .…”
Section: Discussioncontrasting
confidence: 99%
“…3 changes from 46 to 0% when removing the study of Staehr-Rye and colleagues 6 from the meta-analysis. A possible explanation could be that only the studies by Kim and colleagues, 1 Koo and colleagues, 5 and Staehr-Rye and colleagues 6 used low-pressure pneumoperitoneum. Kim and colleagues 1 decreased the IAP from standard pressure (1.6 kPa) without compromising the surgical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some only reported the percentage of unacceptable surgical conditions, which was generally the frequency of scores on the lower half of the surgical rating scale [3, 17, 20]. In addition, the number and moments of scoring differed considerably, with some studies scoring every 10 or 15 min [1, 2, 4, 7, 19, 20], while others scored one overall score at the end of surgery [3, 5, 8, 15, 17, 18, 21]. Some reports do not mention a scoring interval at all [16, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Some reports do not mention a scoring interval at all [16, 24]. In addition to the surgical rating scale, some have assessed other outcomes as well such as intra-abdominal space and the effect on insufflation pressures (see Table 4) [6, 15, 17, 20]. …”
Section: Resultsmentioning
confidence: 99%